Lessons learnt from incidents involving the airway and breathing reported from Australasian emergency departments. (16th August 2017) - Crock, Carmel; Hansen, Kim; Fogg, Toby; Cahill, Angela; Deakin, Anita; Runciman, William B
Abstract: Objective: To review incident reports relating to problems encountered during the ED management of patients with 'airway or breathing' problems, with the aim of finding and highlighting common themes within these rare events, and making recommendations to further improve patient safety in the areas in which deficiencies have been identified. Methods: Thematic analysis of 36 incidents reported from Australasian EDs, which were related to problems with airway and breathing. Results: In all, 51 problems were identified among the 36 incidents related to airway and/or breathing. Fourteen involved clinical decision‐making, 11 equipment, nine communication, seven intubation, five surgical access and five pneumothorax. Eight incidents involved children and there were nine deaths within hours or days. Conclusions: Recommendations for improving preparedness of ED staff and facilities have been made for each of the problem areas identified with respect to clinical practice, equipment, communication and clinical process. Analysis of incidents from the Australasian Emergency Medicine Events Register allows clusters of like‐events to be identified and characterised, providing the possibility of getting a better idea of how problems present and progress, with some information about contributing factors, characteristics and context. This will pave the way for earlier and better detection of life‐threatening problems and the development and reinforcement of preventive and corrective strategies.